Working with and for ancestors
1 online resource (1 volume)
Keywords: "Working with and for Ancestors examines collaborative partnerships that have developed around the study and care of Indigenous ancestral human remains. In the interest of reconciliation, museums and research institutions around the world have begun to actively seek input and direction from Indigenous descendants in establishing collections care and research policies. However, true collaboration is difficult, time-consuming, and sometimes awkward. By presenting examples of projects involving ancestral remains that are successfully engaged in collaboration, the book provides encouragement for scientists and descendant communities alike to have open and respectful discussions around the research and care of ancestral human remains. Key themes for discussion include new approaches to the care for ancestors, the development of culturally sensitive museum policies, the emergence of mutually beneficial research partnerships, and emerging issues such as intellectual property issues, digital data, and alternatives to destructive analyses. Critical discussions by leading scholars also identify the remaining challenges in the repatriation process and offer a means to continue moving forward. This volume will appeal to a broad, interdisciplinary audience interested in collaborative research and management strategies that are aimed at developing mutually beneficial relationships between researchers and descendant communities. This includes students and researchers in archaeology, anthropology, museums studies and, Indigenous communities"--